Astrocytes promote progression of breast cancer metastases to the brain via a KISS1-mediated autophagy. Issue 11 (2nd November 2017) - Kaverina, Natalya; Borovjagin, Anton V.; Kadagidze, Zaira; Baryshnikov, Anatoly; Baryshnikova, Maria; Malin, Dmitry; Ghosh, Dhimankrishhna; Shah, Nameeta; Welch, Danny R.; Gabikian, Patrik; Karseladze, Apollon; Cobbs, Charles; et al.
ABSTRACT: Formation of metastases, also known as cancer dissemination, is an important stage of breast cancer (BrCa) development. KISS1 expression is associated with inhibition of metastases development. Recently we have demonstrated that BrCa metastases to the brain exhibit low levels of KISS1 expression at both mRNA and protein levels. By using multicolor immunofluorescence and coculture techniques here we show that normal adult astrocytes in the brain are capable of promoting metastatic transformation of circulating breast cancer cells localized to the brain through secretion of chemokine CXCL12. The latter was found in this study to downregulate KISS1 expression at the post-transcriptional level via induction of microRNA-345 ( MIR345 ). Furthermore, we demonstrated that ectopic expression of KISS1 downregulates ATG5 and ATG7, 2 key modulators of autophagy, and works concurrently with autophagy inhibitors, thereby implicating autophagy in the mechanism of KISS1 -mediated BrCa metastatic transformation. We also found that expression of KISS1 in human breast tumor specimens inversely correlates with that of MMP9 and IL8, implicated in the mechanism of metastatic invasion, thereby supporting the role of KISS1 as a potential regulator of BrCa metastatic invasion in the brain. This conclusion is further supported by the ability of KISS1, ectopically overexpressed from an adenoviral vector in MDA-MB-231Br cells with silenced expression of the endogenous gene, to revert invasive phenotype of those cells. Taken together, our results strongly suggest that human adult astrocytes can promote brain invasion of the brain-localized circulating breast cancer cells by upregulating autophagy signaling pathways via the CXCL12- MIR345 - KISS1 axis.